Determinants of vaccine hesitancy in Africa: a systematic review - Paone, Alexander (Department of Public Health and Family Medicine, 2018)
This MPH dissertation is a systematic review of the factors contributing to vaccine hesitancy in Africa. The dissertation comprises of the following three parts: The research protocol (Part A) outlines the background and proposed methods of the research. The protocol outlines the search strategy used to identify research eligible for this review according to defined criteria. The objective of this research was to identify determinants of vaccine hesitancy in Africa. The protocol describes data collection methods and the analysis plan of this research in order to address the objective. The literature review (Part B) provides a summary and interpretation of the current literature on barriers to vaccination, specifically vaccine hesitancy and its impacts on immunisation programs. The literature review identifies discord among literature in defining vaccine hesitancy and evaluating its presence and impact on varying populations, and reviews the attempts for standardisation by the Strategic Advisory Group of Experts Working Group on Vaccine Hesitancy. Lastly, the literature review identifies gaps in the literature, and suggests filling them ideally with a standardised metric. The manuscript (Part C) is presented in a format suitable for Vaccine journal submission. The manuscript includes a background, a description of the methods used, and a presentation and discussion of the results of the systematic review.